The Influence of the Principal's Transactional Leadership Style on Student Learning Motivation - Fika Fika; Wiwin Mistiani; Masmur M. (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2026)
The purpose of this study was to investigate and find out the impact of the principal's transactional leadership style on the learning motivation of scale participants at SDN 2 Tilung, Parigi Moutong Regency. Although learning motivation is a major factor influencing student learning motivation, transactional leadership emphasizes the reciprocal interaction between leaders and subordinates through incentive and monitoring systems. Surveys were used in the quantitative methodology of this study to collect data. Forty-five students of SDN 2 Tilung, Parigi Moutong Regency, became a sample. Data analysis, including descriptive analysis, classical assembly testing, and hypothesis testing, was performed using SPSS software version 26. The researchers used a t-test to determine whether principals' transactional leadership had an effect on students' learning motivation. The results showed a significance value of 0.001, which < 0.05. By obtaining the consistency of variable Y of 15.710 and the regression coefficient of X of 0.523, this study also used a linear regression analysis test to determine the extent to which the principal's transactional leadership had a positive relationship with student learning motivation. The results showed that students' enthusiasm for learning was positively and significantly influenced by the principal's transactional leadership by 21.6%. These results show that students' enthusiasm for learning is positively and significantly influenced by the principal's transactional leadership